2014
DOI: 10.1016/j.bbagrm.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

MYC interacts with the human STAGA coactivator complex via multivalent contacts with the GCN5 and TRRAP subunits

Abstract: MYC is an oncogenic DNA-binding transcription activator of many genes and is often upregulated in human cancers. MYC has an N-terminal transcription activation domain (TAD) that is also required for cell transformation. Various MYC TAD-interacting coactivators have been identified, including the transcription/transformation-associated protein (TRRAP), a subunit of different histone acetyltransferase (HAT) complexes such as the human “SPT3-TAF9-GCN5 Acetyltransferase” (STAGA) complex involved in MYC transactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 62 publications
4
27
0
Order By: Relevance
“…A more recent study concluded that global amplification of gene expression might be secondary to the effects of Myc in regulating specific gene targets, especially those related to cell growth and division (Sabo et al 2014). Our data are consistent with previous studies that indicated a role for Myc and E2f1 in SAGA complex recruitment to specific target genes in transformed cells (McMahon et al 1998(McMahon et al , 2000Zhang et al 2014). Furthermore, Myc facilitates global maintenance of active acetylated chromatin and recruits Gcn5 to cell cycle-related genes in neural stem cells (Knoepfler et al 2006;Martinez-Cerdeno et al 2012).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A more recent study concluded that global amplification of gene expression might be secondary to the effects of Myc in regulating specific gene targets, especially those related to cell growth and division (Sabo et al 2014). Our data are consistent with previous studies that indicated a role for Myc and E2f1 in SAGA complex recruitment to specific target genes in transformed cells (McMahon et al 1998(McMahon et al , 2000Zhang et al 2014). Furthermore, Myc facilitates global maintenance of active acetylated chromatin and recruits Gcn5 to cell cycle-related genes in neural stem cells (Knoepfler et al 2006;Martinez-Cerdeno et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…However, recruitment of the SAGA complex with an intact HAT module appears to be key. Trrap and Gcn5 have both been reported to interact directly with Myc (McMahon et al 1998Zhang et al 2014), consistent with our findings (Supplemental Fig. S5B), so these factors likely negotiate recruitment of the SAGA complex to Myc target genes.…”
Section: Discussionsupporting
confidence: 81%
“…These functions include regulating ribosomal protein gene expression and cell growth . Importantly, mammalian TRRAP interacts with and is required for the activity of Myc . These results delineate a link between Myc and TRRAP that is reminiscent of the Sfp1/Tra1 connection observed in yeast.…”
Section: Discussionmentioning
confidence: 65%
“…This inconsistency is partly due to the fact that MYC is able to modulate the transcription of up to 15% of all protein coding genes (8,9). Another layer of complexity is added by the finding that MYC can interact with several proteins able to induce chromatin modifications associated with active transcription, like TRRAP (10), GCN5 (11), and TIP60 (12). MYC was also found bound to components of the P-TEFb complex and to influence general transcriptional pause release (13).…”
Section: Significancementioning
confidence: 99%